2014
DOI: 10.1155/2014/857934
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Media from Microvascular Endothelial Cells Cultured in Simulated Microgravity Inhibit Osteoblast Activity

Abstract: Background and Aims. Gravity contributes to the maintenance of bone integrity. Accordingly, weightlessness conditions during space flight accelerate bone loss and experimental models in real and simulated microgravity show decreased osteoblastic and increased osteoclastic activities. It is well known that the endothelium and bone cells cross-talk and this intercellular communication is vital to regulate bone homeostasis. Because microgravity promotes microvascular endothelial dysfunction, we anticipated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Actin rearrangements of endothelia l cells (Siamwala et al, 2010) Changes in vasoresponsiveness (White et al, 2010) Heart Arrhythmias (Respress et al, 2014) Myocardial abnormalities (Liang et al, 2020) casein kinase-2 interacting protein-1 (CKIP-1) as a Suppressor of cardiac remodeling under microgravity (Ling et al, 2018) Changes of mitochondria, ribosornes, and endoplasmic reticulum in cardiomyocytes (Feger et al, 2016) Impairment of neural crest-derived cardiac structures with alterations in the autonomic nervous system (Hatzistergos et al, 2018) Bone Involvement of matrix metalloproteases type 2 and interleukin-6 in the defect of osteogenesis (Cazzaniga et al, 2014). Role of miR-494 in the defect of osteogenesis (Qin et al, 2019).…”
Section: Vesselsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin rearrangements of endothelia l cells (Siamwala et al, 2010) Changes in vasoresponsiveness (White et al, 2010) Heart Arrhythmias (Respress et al, 2014) Myocardial abnormalities (Liang et al, 2020) casein kinase-2 interacting protein-1 (CKIP-1) as a Suppressor of cardiac remodeling under microgravity (Ling et al, 2018) Changes of mitochondria, ribosornes, and endoplasmic reticulum in cardiomyocytes (Feger et al, 2016) Impairment of neural crest-derived cardiac structures with alterations in the autonomic nervous system (Hatzistergos et al, 2018) Bone Involvement of matrix metalloproteases type 2 and interleukin-6 in the defect of osteogenesis (Cazzaniga et al, 2014). Role of miR-494 in the defect of osteogenesis (Qin et al, 2019).…”
Section: Vesselsmentioning
confidence: 99%
“…Interestingly, in microgravity, rapamycin induces transcriptional activation of blood-derived stem cells towards osteogenic differentiation by influencing bone formation (Gambacurta et al, 2019). Moreover, due to the delay of microvascular endothelial cell growth and the release of a high amounts of matrix metalloproteases type 2 and interleukin-6, the growth of osteoblasts is retarded and their osteogenic activity is impaired (Cazzaniga et al, 2014). Also miR-494 is correlated with a decrease in osteogenesis due to a marked reduction in osteoblast differentiation genes (Qin et al, 2019).…”
Section: Brainmentioning
confidence: 99%
“…[13][14][15][16] We have also shown that microvascular endothelial cells in simulated microgravity release proteins that affect osteoblast behavior in a co-culture system. 17 Recently, both macrovascular 18 and microvascular endothelial cells were flown to the International Space Station (ISS), which offers unique opportunities to study the effect of space on the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among the bioreactors, the rotating wall vessel (RWV), a suspension culture system that permits the cultivation of cells under low physiological fluid shear conditions, has been widely utilized [ 5 , 6 ]. The RWV requires to grow adherent cells on microcarrier beads so that they rotate at the same speed of the vessel wall around a horizontal axis, a condition that produces a vector-averaged gravity comparable with that of the near-earth free-fall orbit [ 7 ].…”
Section: Introductionmentioning
confidence: 99%